Physical Connectivity Between the NE Atlantic Seamounts - Lima, Maria João; Sala, Iria; Caldeira, Rui M. A. (Frontiers in Marine Science, 2020)
Within the Portuguese Exclusive Economic Zone, the Great Meteor and Madeira-Tore complexes are highly productive areas, which are likely to be classified as Marine Protected Areas due to their ecological vulnerability. This was the main focus of the BIOMETORE project and framed on it, the aim of the present study was to investigate the physical connectivity between both seamount complexes. Using the Hybrid Coordinate Ocean Model coupled with the Connectivity Modeling System (a Lagrangian tool), a series of experiments were conducted in order to determine the influence of the main oceanographic phenomena governing the area in: i) the origin of the particles that reach each complex, ii) their capacity to capture and retain incoming particles, and (iii) the physical connectivity between them, as well as the intra-connectivity within each seamount system. Due to the geographical location of both groups of seamounts, the Azores Current (AzC) and its associated eddies were identified as the main transport pathways, being its influence stronger at intermediate waters, decreasing with depth. Notwithstanding, the Great Meteor and the Madeira-tore were mainly affected by the AzC southward and eastward branch, respectively, resulting in a non-significant connectivity between the two groups. Meanwhile, the inter-connectivity between seamounts slightly varied with depth at Great Meteor complex, while increasing at Madeira-Tore. In addition, Plateau, Irving and Cruiser (PIC) seamounts from the Great Meteor complex, and Gorringe and Coral from the Madeira-Tore complex proved to incorporate the main connectivity routes in the studied area. Although containing the three smallest seamounts, Madeira-Tore showed the higher capturing capacity per km2, highlighting the influence of the ‘Sticky Water Effect’. In the Great Meteor complex, the ‘Seamount Effect’ seems to be the main phenomenon responsible for the greater retention and self-recruitment abilities of these seamounts. The presented results provide valuable information for the design of an MPA to preserve these vulnerable habitats.